Surgical dilemma: Exomphalos major with accessory liver lobe and congenital liver cysts - Nicola Cullen; Mohamed A Alagtal; Angela T Byrne; Brice Antao (Wolters Kluwer Medknow Publications, 2022)
The association of exomphalos major, congenital liver cysts, and an accessory lobe of the liver is very rare. There are only two previously reported cases in the literature, both describing surgical excision of the accessory lobe with liver cysts during primary closure of the exomphalos defect. We report a case of this rare association, managed by delayed primary closure, where the cysts underwent spontaneous regression. This case, along with those previously reported, supports the etiopathogenesis theory of a malformative sequence of exomphalos and hepatic trauma within the sac of this rare association. Spontaneous regression of these cysts would favor a delayed primary closure in such cases.